2021
DOI: 10.26803/ijlter.20.3.7
|View full text |Cite
|
Sign up to set email alerts
|

Success Indicators of Mathematical Problem-Solving Performance Among Malaysian Matriculation Students

Abstract: This study identifies the success indicators of mathematical problem-solving performances among Malaysian matriculation students divided into four indicators: mathematical beliefs, mathematics attitudes, mathematics self-efficacy and metacognitive skills. For this purpose, 368 matriculation students from three matriculation colleges were selected as respondents using proportioned stratified sampling. This study utilized a descriptive correlational design approach. A set of questionnaires and a mathematics test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…Thus, teachers cannot overlook the need to promote the development of meta-cognitive skills (e.g., predicting, monitoring, and evaluating the problem-solving process) in conjunction with self-efficacy beliefs to raise learners' mathematics achievement subsequently. Bakar et al (2021) and Kaskens et al (2020) report an insignificant relationship between mathematics self-efficacy and problem-solving achievement. In particular, Bakar et al (2021) observed metacognitive skills, mathematics attitude, and mathematics beliefs as more significant contributors to mathematics problem-solving achievement than self-efficacy.…”
Section: Theoretical Backgroundmentioning
confidence: 93%
See 2 more Smart Citations
“…Thus, teachers cannot overlook the need to promote the development of meta-cognitive skills (e.g., predicting, monitoring, and evaluating the problem-solving process) in conjunction with self-efficacy beliefs to raise learners' mathematics achievement subsequently. Bakar et al (2021) and Kaskens et al (2020) report an insignificant relationship between mathematics self-efficacy and problem-solving achievement. In particular, Bakar et al (2021) observed metacognitive skills, mathematics attitude, and mathematics beliefs as more significant contributors to mathematics problem-solving achievement than self-efficacy.…”
Section: Theoretical Backgroundmentioning
confidence: 93%
“…Bakar et al (2021) and Kaskens et al (2020) report an insignificant relationship between mathematics self-efficacy and problem-solving achievement. In particular, Bakar et al (2021) observed metacognitive skills, mathematics attitude, and mathematics beliefs as more significant contributors to mathematics problem-solving achievement than self-efficacy.…”
Section: Theoretical Backgroundmentioning
confidence: 93%
See 1 more Smart Citation
“…Studies on metacognition in problem-solving have significantly progressed, particularly in mathematics education (Kayashima et al, 2005;Laamena & Laurens, 2021;Permadi & Irawati, 2023). Previous research has shown that metacognition plays a crucial role in determining the success or failure of solving mathematical problems (Bakar et al, 2021;Gurat & Medula Jr, 2016;Kaune et al, 2011;Magiera & Zawojewski, 2011;Ozturk, 2016;Panaoura & Philippou, 2005). Metacognition, as explained by Flavell (1979), refers to cognitive processes involving individual awareness of the acquisition of knowledge and the ability to organise knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Through this capacity, individuals will comprehend and be able to employ numerous ways to solve mathematical issues (Gavaz et al, 2021;Marchiş, 2013;Phonapichat et al, 2014). MPSS comprises a person's capacity to adapt numerous tactics and strategies from previously learned activities to find the optimal answer to a new problem or situation (Bakar et al, 2021;Schoenfeld, 1982). By teaching MPSS, students can become accustomed to being able and skilful in comprehending the many challenges encountered, developing diverse problem-solving methodologies, and being aware of the necessity of re-examining previously achieved solutions.…”
Section: Introductionmentioning
confidence: 99%